Impact of a Hypnotically-Based Intervention on Pain and Fear in Women Undergoing Labor. Issue 1 (2nd January 2017) - Waisblat, Véronique; Langholz, Bryan; Bernard, Franck J.; Arnould, Monique; Benassi, Aurélien; Ginsbourger, François; Guillou, Nicolas; Hamelin, Karine; Houssel, Philippe; Hugot, Pierre; Martel-Jacob, Sylvie; Moufouki, Moustapha; et al.
Abstract: The purpose of this study was to evaluate the effects of a hypnotically-based intervention for pain and fear in women undergoing labor who are about to receive an epidural catheter. A group of 155 women received interventions that included either (a) patient rocking, gentle touching, and hypnotic communication or (b) patient rocking, gentle touching, and standard communication. The authors found that the hypnotic communication intervention was more effective than the standard communication intervention for reducing both pain intensity and fear. The results support the use of hypnotic communication just before and during epidural placement for women who are in labor and also indicate that additional research to evaluate the benefits and mechanism of this treatment is warranted.